The role of scientific and technical data and information in the public domain : proceedings of a symposium - Esanu, Julie M.; Uhlir, P. F. (Paul F.), 1954- (National Academies Press, 2003)
The body of scientific and technical data and information (STI) in the public domain in the United States is massive and has contributed broadly to the economic, social, and intellectual vibrancy of the nation. The "public domain" can be defined in legal terms as sources and types of data and information whose uses are not restricted by statutory intellectual property laws or by other legal regimes, and that are accordingly available to the public for use without authorization. In recent years, however, there have been growing legal, economic, and technological pressures that restrict the creation and availability of public-domain information -- scientific and otherwise. It is therefore important to review the role, value, and limits on public-domain STI. The meeting brought together leading experts and managers from the public and private sectors who are involved in the creation, dissemination, and use of STI to discuss (1) the role, value, and limits of making STI available in the public domain for research and education; (2) the various legal, economic, and technological pressures on the producers of public-domain STI and the potential effects of these pressures on research and education; (3) the existing and proposed approaches for preserving the STI in the public domain or for providing "open access" in the United States; and (4) other important issues in this area that may benefit from further analysis.